Corporate Hypocrisy, CSR and Organisational Identification Role in Engagement and Innovation Work Behaviours - A.B.Bekmukhametova; J. Jappar (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The purpose of this study, which was carried out in a significant corporate bank in Kazakhstan, is to clarify the dynamics of innovative behaviors and work engagement by examining organizational identification, corporate social responsibility (CSR), and corporate hypocrisy. Methodology: Using a simple random sample technique, the study examines the work behaviors of 247 managers. The study takes a cross-sectional approach and uses Smart PLS for analysis to look at the complex correlations between these factors. Findings: The results show that perceived corporate hypocrisy has a positive and significant impact on work engagement and innovative work behavior. As well as moderating the role of perceived CSR on perceived corporate hypocrisy, work engagement, innovative work behavior, and significant moderating impact of organizational identification. Thus, all organizations require innovative people who can provide novel and valuable ideas. Implications/Novel Contribution: From an organizational perspective, an organization expects its employees to fulfill their formal job requirements and volunteer to engage in various supplementary tasks, such as being innovative, navigating an uncertain environment, and creating sustained competitive advantage.